The effect of a hybrid coating of porous silicon and WS2 and MoS2 quantum dots on the electrical characteristics of photosensitive structures - Natalia A. Poluektova; Daria A. Shishkina; Danil P. Grigoriev (Физика волновых процессов и радиотехнические системы)
Background. This paper examines the effect of the hybrid coating of quantum dots and porous silicon on the volt-ampere characteristic of photosensitive structures. The object of the study was silicon solar cells with a porous layer and WS2 and MoS2 quantum dots. Increasing the energy efficiency of solar panels is an urgent task due to the high demand for alternative energy sources. Quantum dots, due to the properties of nanoscale structures, in combination with a layer of micro- and nanopores, can contribute to increased efficiency. Aim. Creation of photosensitive structures with porous silicon and quantum dots and subsequent investigation of their volt-ampere characteristics to identify the nature of the interaction of quantum dots with porous structures. Methods. Empirical and analytical methods were used in this work. Results. The volt-ampere characteristics of photosensitive structures are obtained. The dependence of the increase in saturation current values on the etching time and the depth of the quantum dots is revealed. Conclusion. The hybrid coating of porous silicon and WS2 and MoS2 quantum dots has a positive effect on the electrical characteristics of solar cells. However, further research is required on the dependence of increasing the efficiency of solar cells on the volume of applied quantum dots.